Numerical Study of Deflection and Stress Distribution on Composite Box Spar Structure – Application In Wind Turbine Blade - Putri Safina Ufaira; Putu Suwarta; Galih Bangga (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2022)
This paper present ﬁnite element analysis on the internal structure of wind turbine to examined the deﬂection and stress distribution. The structure was modeled as a cantilever box beam with constant cross section along the length. The dimension of the structure was set according to the original design of the 10 MW AVATAR (Advanced Aerodynamic Tools for Large Rotors) wind turbine. The proposed materials were unidirectional thin-ply TC35/Epoxy and M55/Epoxy carbon composites and standardthickness S−Glass 913/Epoxy composite. The ﬁbre at the spar caps is oriented at 90o and at the shear webs at 0o. The deﬂection curve of the three composite materials showing non-linear behaviour with a maximum deﬂection of 2.618 m, 2.429 m, 4.175 m at the blade tip for S−Glass 913/Epoxy, T35/Epoxy, M55/Epoxy respectively which is less than the maximum deﬂection of an existing AVATAR beam. The critical stresses are located at the top outer surface of the spar cap which received the load directly and at the intersection between the spar caps and shear webs where stress transfer occurs. The deﬂection performance of the structure is dictated by the transverse Young’s Modulus (E22) while the longitudinal Young’s Modulus (E11) plays an important role on stress distribution.